An updated analysis on the association of GSTM1 polymorphism and smoking exposure with the increased risk of coronary heart disease. Issue 9 (September 2022) - Liu, Min; Gu, Ye; Ma, Jian-Ning; Bao, Ke-Na; Ao, Li; Ni, Xin
Objective: To undertake a meta-analysis to investigate if there is an association between the glutathione S-transferase mu 1 ( GSTM1 ) gene polymorphism, coronary artery disease (CAD) susceptibility and smoking. Methods: Electronic databases, including PubMed®, Web of Science and Embase®, were searched for relevant case–control studies. Data were extracted and the odds ratio (OR) was calculated and appropriate statistical methods were used for the meta-analysis. Results: The analysis included eight studies with a total of 1880 cases with CAD and 1758 control subjects. The results of this meta-analysis demonstrated that there is no association between the GSTM1 null and CAD (OR 1.24, 95% confidence interval [CI] 1.00, 1.55). An increased risk of CAD was observed in the smoking population with the GSTM1 null genotype (OR 1.48, 95% CI 1.02, 2.15). Subgroup analyses of geographical region, genotyping method and publication language category demonstrated potential relationships among gene polymorphism, smoking and CAD. Conclusions: Based on the current literature, the GSTM1 null genotype was associated to CAD in the smoking population. The interaction between smoking and GSTM1 polymorphism may contribute to the susceptibility of CAD.